Load management for Voltage Stability control in multi-area power system - Mustaffa S.A.S.; Musirin I.; Othman M.M.; Salimin R.H. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer programming; Control system stability; Control systems; Electric load management; Electric power plant loads; Electric power system control; Electric power system stability; Evolutionary algorithms; Power control; Reactive power; Stability; System stability; Voltage control; Fast voltage stability indices; Loading condition; Multi area power systems; Optimization techniques; Power system networks; Voltage security assessment; Voltage stability assessment; Voltage stability controls; Loading